Pelatihan Manajemen Kedaruratan Dasar Bagi Kader Kesehatan: Basic Emergency Management Training for Health Cadres - Kamesyworo, Kamesyworo; Hartati, Sri; Haryant, Eka (Chakra Brahmanda Lentera Institute, 2025)
Emergency situations are sudden events that require immediate action. These conditions can arise from trauma or non-trauma incidents, with risks of respiratory arrest, cardiac arrest, organ damage, or bleeding. Emergencies can occur to anyone, at any time, and anywhere, characterized by their rapid onset and unpredictability. Quick, accurate, and careful management of emergencies is crucial to prevent death and disability, in line with the principle that